DOP55 Long-term outcomes after histologic-endoscopic mucosal healing: Results from the UNIFI study in Ulcerative Colitis. (21st January 2022) - Leong, R; Sands, B; Peyrin-Biroulet, L; Marano, C; Miao, Y; Izanec, J; Feagan, B; Rubin, D
Abstract: Background: In the UNIFI study of ustekinumab (UST) in ulcerative colitis (UC), patients who achieved histo-endoscopic mucosal healing (HEMH; ie, both histologic and endoscopic improvement of mucosa) after induction had higher clinical remission and corticosteroid-free clinical remission rates through 1 year than those who achieved either histologic or endoscopic improvement alone. 1 Here, we report the effect of achieving HEMH after induction on long-term symptomatic outcomes through 3 years. Methods: Patients who were in clinical response after 8 wks of IV induction with UST 130mg or 6mg/kg (wk 8 responders) were randomized to maintenance treatment with SC UST 90mg q12w or q8w on entry into maintenance. Those who were not in clinical response to the initial UST dose at wk8 but achieved response at wk16 after receiving a single SC dose of UST 90mg at wk8 (wk16 responders) entered maintenance receiving SC 90mg q8w. After 44 wks of maintenance treatment, patients were given the option to continue in the long-term extension. HEMH was defined as achieving both endoscopic improvement (Mayo endoscopy subscore ≤1) and histologic improvement (neutrophil infiltration in <5% of crypts, no crypt destruction, and no erosions, ulcerations, or granulation tissue; based on the Geboes score). Patients with insufficient data for histologic evaluation at the end of induction were excluded. Symptomatic remission was defined as a Mayo stool frequency subscore of 0 or 1 and a Mayo rectal bleeding subscore of 0. Results: Of the 438 patients who were wk8 or wk16 responders to UST induction and received UST maintenance, 116 (26.5%) achieved HEMH after induction, 30 (6.8%) achieved endoscopic improvement without histologic improvement (EI), and 106 (24.2%) achieved histologic improvement without endoscopic improvement (HI). Patients who achieved HEMH after induction had higher symptomatic remission and corticosteroid-free symptomatic remission rates at wks92 and 152 than those with EI or HI; the differences were statistically significantly greater at wk152, while they were only numerically greater at wk92 (Table). The differences were primarily driven by patients with HEMH after induction being more likely to maintain symptomatic remission between wks92 and 152, than those with EI or HI alone. Symptomatic remission and corticosteroid-free remission rates decreased between wks92 and 152 in patients with EI or HI only. Conclusion: Patients with UC who achieved HEMH after induction with UST were more likely to maintain symptomatic remission and corticosteroid-free symptomatic remission between 2 and 3 years of maintenance treatment than those who achieved EI or HI alone. Reference: 1. K Li, et al. Poster 1008. Presented at UEGW 2019. October 22, 2019. Barcelona, Spain.